Novel electrochemical and electrochemiluminescence dual-modality sensing platform for sensitive determination of antimicrobial peptides based on probe encapsulated liposome and nanochannel array electrode - Luo, Xuan; Zhang, Tongtong; Tang, Hongliang; Liu, Jiyang (Frontiers in Nutrition, 2022)
With the increasing application of antimicrobial peptides (AMPs) to replace antibiotics in medicine, food and agriculture, it is highly desired to develop a fast, reliable, and convenient strategy for sensitive detection of AMPs. Herein, a novel electrochemical (EC) and electrochemiluminescence (ECL) dual-modality sensing platform was developed based on probe encapsulated liposomes and nanochannel array modified electrodes, which enables sensitive determination of nisin in food samples. Liposomes encapsulating EC and ECL bifunctional probe Ru(bpy)32+ were prepared to serve as the sensing and signaling components. Based on the unique sterilization mechanism of AMPs disrupting cell membranes, tris(2,2-bipyridyl) dichlororuthenium (II) encapsulated liposomes (Ru(bpy)32+@liposome) can be destroyed by nisin and release a large number of Ru(bpy)32+ probes. Vertically-ordered mesoporous silica-nanochannel film (VMSF) modified ITO (VMSF/ITO) electrodes prepared by electrochemically assisted self-assembly (EASA) method were applied as the sensing electrode. Due to the efficient enrichment of Ru(bpy)32+ by the nanochannel arrays, VMSF/ITO enables detection of the EC/ECL signals of the released Ru(bpy)32+ probes with ultrahigh sensitivity. In consequence, sensitive dual-modality detection of nisin was achieved by the combination of Ru(bpy)32+@liposome and VMSF/ITO. The developed sensing system can realize sensitive determination of nisin in ECL mode in the concentration range of 10 ng/mL to 50 μg/mL with a limit of detection (LOD) of 9.3 ng/mL, or in EC mode from 800 ng/mL to 100 μg/mL with an LOD of 70 ng/mL. Combined with the excellent antifouling and anti-interference performance of VMSF, rapid and sensitive detection of nisin in milk or egg white was also achieved by the sensor.